2009
DOI: 10.1177/0142723708101680
|View full text |Cite
|
Sign up to set email alerts
|

Five-year-olds' book talk and story retelling: Contributions of mother—child joint bookreading

Abstract: This study examined the participation of preschool children (mean age 5;1) in two literacy-related activities — talking about a book with their mothers and subsequent independent retelling of the story. Sixty-two mother—child dyads from low-income families participated. Analysis of bookreading and story retelling transcripts revealed wide variability in extratextual talk during bookreading by both children and mothers. Children's responsive, but not spontaneous, extratextual book talk was closely associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 47 publications
2
57
1
1
Order By: Relevance
“…Our findings further suggested that mothers' book‐sharing styles are associated with individual and ethnic variations in children's storytelling styles. Our findings highlighted the role of questions – characteristic of a dialogic style – for children's narrative development (Cristofaro & Tamis‐LeMonda, ; Kang et al, ; Melzi & Caspe, ; Reese & Newcombe, ). At the individual level, mothers' questions were associated with children's narrative contributions during book‐sharing.…”
Section: Discussionsupporting
confidence: 56%
“…Our findings further suggested that mothers' book‐sharing styles are associated with individual and ethnic variations in children's storytelling styles. Our findings highlighted the role of questions – characteristic of a dialogic style – for children's narrative development (Cristofaro & Tamis‐LeMonda, ; Kang et al, ; Melzi & Caspe, ; Reese & Newcombe, ). At the individual level, mothers' questions were associated with children's narrative contributions during book‐sharing.…”
Section: Discussionsupporting
confidence: 56%
“…First, the results indicated that a child's engagement with literal text representation was related to his or her buddy's engagement with literal text representation. Thus, modelling the use of literal text representation in the preschool buddy‐reading context can be effective, similar to the effectiveness of modelling that occurs during adult–child joint reading (e.g., Danis et al, ; Hammett, Bradley & van Kleeck, ; Kang et al, ; Moschovaki et al, ; Zucker et al, ). Second, children's engagement with comprehension monitoring, such as agreeing, was related to their buddies’ engagement with inferential interpretations of text.…”
Section: Discussionmentioning
confidence: 85%
“…Another shortcoming of this study was that it did not consider home and school language practices, although they may be related to the children's overall oral language production skills. For example, the number of books available at home and the frequency: and quality of parent-child joint böokreading play an important role in children's overall language and hteracy development (Kang, Kim, & Pan, 2009;Snow, 1983), and "the most important facilitator of narrative development turns out to be the extent to which parents are sensitive to their children's conversational attempts" (Verhoeven & Strömqvist, 2001, p.6), but such information was not considered in this study. Finally, since wordless picturebook elicitation may have eliminated potential cultural differences in story organization and structuring, and since "narrative assessments that seem comparable may pose different processing demands on bilingual speakers" (Uccelli and Páez, 2007), différent elicitation strategies should be considered in future studies, especially since previous studies, as well as the current study, mostly relied on the "frog story" or similar picture-elicited narratives and personal narratives (Berman & Slobin, 1994;Hickmann et al, 1996;Kang, 2003;2004;Muñoz et al, 2003;Uccelli & Páez, 2007).…”
Section: Discussionmentioning
confidence: 99%